Two-way shear strength of reinforced concrete transfer slab-column connections. (15th March 2021) - Kang, Su-Min; Na, Su-Jeong; Hwang, Hyeon-Jong
Highlights: Compression tests were performed to investigate the two-way shear strength of RC transfer slabs. The two-way shear strength was increased by high-strength concrete and high-rebar ratio. Early shear failure occurred in thick transfer slab without uniformly distributed slab rebars. A strut-tie method was proposed to predict the two-way shear strength of RC transfer slabs. Abstract: In high-rise wall-type residential buildings, thick RC transfer slabs have been widely used for parking space or public space. Despite the different behavior from thin RC flat slab, design methods for thin RC flat slab are applied to the thick RC transfer slab, due to the limited literature on the two-way shear behavior of RC transfer slab systems with small shear span-to-depth ratio. In the present study, concentric compression tests were performed on eight RC transfer slabs with small shear span-to-depth ratio to investigate the two-way shear strength. The test parameters were the concrete strength, shear span-to-depth ratio, slab thickness, and reinforcement ratio of the slab. The two-way shear strength, deformation capacity, failure mode, and strain distribution of slab rebars of the slab specimens were evaluated. The test results showed that the use of high-strength concrete or large reinforcement ratio increased the two-way shear strength of the transfer slab specimens. However, the transfer slab specimen having large slab thickness without sufficient reinforcement was susceptible to punching shear failure, showing insignificant strength increment. The two-way shear strengths of the test specimens were compared with the predictions of the current design method and the strut-tie model.